2022
DOI: 10.1111/desc.13247
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of self‐regulation in infants at elevated likelihood for autism spectrum disorder

Abstract: Research concerning temperament in children and adults with autism spectrum disorder (ASD) has suggested a consistent profile of low positive affect, high negative affect, and low regulation (Visser et al., 2016). One area receiving less attention is individual differences among children diagnosed with ASD. The primary objective of this study was to use a person‐centered approach to explore heterogeneity of early temperament precursors of regulation in a large sample of infants with elevated familial likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In turn, the development of self-regulatory skills likely impacts on several aspects of child development. In particular, using a person-centered approach to explore heterogeneity of early temperament precursors of regulation, Garon et al (2022) found a three-profile solution (well-regulated, low attention focus, and low attention shifting) during infancy and toddlerhood, and a higher proportion of children diagnosed with ASD were classified into the low attention shifting profile. These findings suggest that the combination of early positive affect with attention measures may provide an enhanced tool for prediction of self-regulation and later outcomes.…”
mentioning
confidence: 99%
“…In turn, the development of self-regulatory skills likely impacts on several aspects of child development. In particular, using a person-centered approach to explore heterogeneity of early temperament precursors of regulation, Garon et al (2022) found a three-profile solution (well-regulated, low attention focus, and low attention shifting) during infancy and toddlerhood, and a higher proportion of children diagnosed with ASD were classified into the low attention shifting profile. These findings suggest that the combination of early positive affect with attention measures may provide an enhanced tool for prediction of self-regulation and later outcomes.…”
mentioning
confidence: 99%
“…Thus, the relationship between ASD and temperament may be driven by the presence of internalizing/externalizing behaviors. Second, although IL siblings with ASD show lower scores on developmental scales (such as Mullen, 1995 ) compared to IL siblings without ASD ( Longard et al, 2017 ), and these scores are related to temperament profiles ( Garon et al, 2022 ), the Expressive and Receptive Language subscales did not affect any of the relationships between temperamental subscales at 6, 12, and 24 months (or temperament profile) and internalizing and externalizing problem scales. Therefore, the relationship between temperament and the presence of internalizing/externalizing behaviors does not appear to be influenced by developmental ability.…”
Section: Discussionmentioning
confidence: 99%
“…Latent profile analysis (LPA) was used to identify groups of children who differed on temperament measures of attention and positive affect using scores from two scales at 6 and 12 months (Duration of Orientation and Smiling/Laughter) and three scales at 24 months (Attentional Focusing, Attentional Shifting, Positive Anticipation). To be included in the LPA analyses, at least one temperament questionnaire had to be completed at 6, 12, and/or 24 months ( Garon et al, 2022 ). As recommended by Masyn (2013) , four different specifications of the variance-covariance structure were used to select the best fit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations